Language Culture Communication - Kijko, Maciej (Journal of Applied Cultural Studies, 2016)
The aim of the study is to outline the role of language as the most effective tool of communication accessible to human beings in the context of international communication. Intercultural communication allows to indicate the diversity of intentions with which we enter into communicative relationships. It also highlights the need to take into account cultural difference in order to achieve understanding: the greater the extent to which diversity is taken into account and the greater the accompanying effort to reconstruct cultural beliefs, the higher the efficiency of communication.